'It's different, but it's the same': perspectives of young adults with siblings with intellectual disabilities in residential care. (12th July 2016) - Jacobs, Paula; MacMahon, Ken
Abstract : Accessible summary: Siblings often play important roles in the lives of people with intellectual disabilities. This study suggests that young adults who have siblings in residential care can feel isolated in their experience. Adolescence appears to be a turning point and a time when siblings become aware of future caretaking responsibilities. There is a need for support for siblings of children and adults with intellectual disabilities who live in residential care. Abstract: Background: Siblings often play significant roles in the lives of people with intellectual disabilities. This study aimed to give voice to young adults whose siblings have an intellectual disability and are in residential care. Materials and Methods: Six participants were interviewed, with interpretative phenomenological analysis methodology employed. Results: Emergent themes included family and sibling relationships and concerns for the future. However, ambivalence, in terms of conflicting feelings within participants themselves, was striking. Dissonances within narratives included identifying as 'one family' whilst living apart, experiencing guilt while being supportive of the residential placement, and emphasising the normality of the sibling experience whilst also feeling different and isolated. Conclusion: These findings reflect the particular complexity of sibling relationships when the person with an intellectual disability lives in residential care. There is a need to understand more about the perspectives of siblings, and the influence that residential care may have upon these.